Assessment of the Effectiveness of Panoramic Radiography and Three-Dimensional Dental Volumetric Tomography with Determination of Implant Size and Position of Bone in Undercuted Regions during Implant Planning - ATALI, ONUR (AVES PRESS LTD, 2018)
Objective: To detect and compare differences in implant length, diameter, and position angle application during implant planning, which dentists make full use of intraoral photography, plaster model, and two-dimensional panoramic radiographs (OPTGs), and review only in Three Dimensional Dental Volumetric Tomoghraphies (3DDVTs). Methods: Three dentistry students were asked to perform implant planning observing the intraoral photographs of patients, model casts, and OPTGs and a digital environment with only 3DDVTs. Differences between previous and subsequent measurements were statistically examined in 35 different records by all participating dentistry students individually and as a whole. Results: There was a statistically significant difference between implant length (p=0.028), thickness (p=0.001), and angular positioning (p=0.001) when evaluating OPTG records, model casts, and intraoral photograph data via 3DDVTs as a whole and individually. Conclusion: It is important to use 3DDVTs for implant planning in the mandibular molar region.
Keywords: Panoramic radiography; three dimensional dental volumetric tomography; implant planning; POSTERIOR MANDIBULAR IMPLANTS; INTERFORAMINAL REGION; BLEEDING COMPLICATIONS; PLACEMENT; SURGERY; DENTISTRY; ACCURACY